Preservation And Revitalization Of Palembang Malay Language Through Traditional Art Of Dulmuluk - Emawati Emawati (Universitas Nahdlatul Wathan Mataram, 2022)
This study was an ethnography study aimed to describe in depth on the preservation and revitalization of Palembang Malay language in Palembang through the traditional art of Dulmuluk. The data were collected by using interviews, observations, field notes, document studies, questionnaires, and photography. The data analysis was done by using the ethnography method of Spradley’s Developmental Sequence Research. The steps of the research were; (1) determination of focus, (2) requesting questions, (3) data collection, (4) analyzing and interpreting data. In addition, the researcher analyzed the field notes from observation on the participants to find out questions and then analyzed the field notes. There are four types of analysis that had been done namely; domain, taxonomic, component and theme analysis. Based on the analysis, the research result shows that in the traditional art of Dulmuluk, Palembang Malay language is still being preserved. The Palembang Malay language still dominates the language uses in the traditional art of Dulmuluk. It is also found that the traditional art of Dulmuluk is being faded away due to the monotonous of the story’s plot and less adapted to the development and the change of the current era so that it is hard for the traditional art of Dulmuluk to compete with the modern art. The effort that can be done to preserve and revitalize the traditional art of Dulmuluk is to create the story with the theme that is relevant to the development and the change of the current era. If it is succeed, it will also affect the preservation of Palembang Malay language. Therefore, the shift and the extinction of the Palembang Malay language can be avoided.